ANTI-BACTERIAL ACTIVITY TESTING OF ETHANOL EXTRACT 96% PAINAGE SKIN (ANANAS COMOSUS (L.) MERR) AGAINST ESCHERICHIA COLI BACTERIA) - . S, Aminah; Abdilantri, Dewi (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2022)
Pineapple peel (Ananas comosus (L.) Merr) is waste form the pineapple fruit. The purpose of this study was to determine the content of pineapple peel extract and to antibacterial activity in various concentrations effective in inhibiting the growth of Escherichia coli. Escherichia coli is a bacterium that generally lives in the large intestine of humans can become a pathogen when it reaches tissues outside the digestive tract which can cause diarrheal disease. The pineapple peel extract is made by using the ectraction method in the form of meceration. The method used in the inhibitory test using the two replication sampels in each treatment groups. The samples consisted of 6 treatment groups is pineapple peel extract concentration 25mg/ml, 50mg/ml, 75mg/ml, and 100mg/ml, as well as positive and negative control. The results obtained from pineapple screening contain alkaloi, flavonoid, tanin, and saponin compounds. The data analysis showsthat pineanepple peel extract concentrations of 25mg/ml, 50mg/ml, 75mg/ml, and 100mg/ml had inhibitory sones with the medium-strong category while ciproloxacin as the control has a strong inhibition zone. The conclusion that while the extract concentration increases, the diameter of the inhibition zone increases.